Theoretical analysis of reinforcement layers in bonded flexible marine hose under internal pressure. (1st August 2018) - Zhou, Yang; Duan, Menglan; Ma, Jianmin; Sun, Guomin
Highlights: An analytical model on reinforcement layers of bonded flexible marine hose under internal pressure is proposed. The derivation is clearly and detailedly demonstrated to show the principle of the mechanical model. A unified mathematical approach which can be suitable for arbitrary multi-layers composite of synthetic fibers in reinforcement structure is set up. The theoretical results explain the variations of stresses and strains of the filament-wound composite, parametric and failure analysis are included to verify the utilization of reinforcement layers. Abstract: This paper portrays the results of analytical study on reinforcement layers of bonded flexible marine hose under internal pressure. Based on the anisotropic laminated composite theory, a complete theoretical solution is chosen to elaborate on the mechanical behaviour of the convoluted reinforcement layers. The developed method aims to set up a unified mathematical approach which can be suitable for arbitrary multi-layers composite of synthetic fibers in reinforcement structure. Comparative case studies are made to verify the accuracy of the method which are in agreement with the published results of four layered filament-wound composite pipe. An extended case study on a typical fourteen-layered reinforcement structure is carried out for investigating the variations of stresses and strains. Furthermore, considering the practical application in offshore engineering, parametric analysis on different known conditions, verification with experimental and numerical results are applied. Failure analysis on Tsai-Hill failure criterion are also proposed to analyze the capability of practical reinforcement layers in bonded flexible marine hose.